mTOR pathway: A key player in diabetic nephropathy progression and therapeutic targets - Jingxuan Shi; Xinze Liu; Yuanyuan Jiao; Jingwei Tian; Jiaqi An; Guming Zou; Li Zhuo (Genes and Diseases)
Diabetic nephropathy is a prevalent complication of diabetes and stands as the primary contributor to end-stage renal disease. The global prevalence of diabetic nephropathy is on the rise, however, due to its intricate pathogenesis, there is currently an absence of efficacious treatments to enhance renal prognosis in affected patients. The mammalian target of rapamycin (mTOR), a serine/threonine protease, assumes a pivotal role in cellular division, survival, apoptosis delay, and angiogenesis. It is implicated in diverse signaling pathways and has been observed to partake in the progression of diabetic nephropathy by inhibiting autophagy, promoting inflammation, and increasing oxidative stress. In this academic review, we have consolidated the understanding of the pathological mechanisms associated with four distinct resident renal cell types (podocytes, glomerular mesangial cells, renal tubular epithelial cells, and glomerular endothelial cells), as well as macrophages and T lymphocytes, within a diabetic environment. Additionally, we highlight the research progress in the treatment of diabetic nephropathy with drugs and various molecules interfering with the mTOR signaling pathway, providing a theoretical reference for the treatment and prevention of diabetic nephropathy.